Synthesis and Mechanistic Study of Hybrid Nanoflower Incorporated Lipase as Biocatalyst for Biodegradation of Bioplastic - Anboo, Shamini (Curtin University, 2023)
Enzyme-incorporated hybrid nanostructures are the immobilization of enzymes and inorganic components which exhibits promising characteristics. The optimum conditions for magnetic hybrid nanoflowers (mhNFs) are growth time 7 mins, lipase concentration 0.3 mg/mL at 30 °C and pH 7.2. The PET biodegradation study showed optimal conditions were at 40 °C, 40 mg of mhNFs and 7 days of reaction. The reusability study showed that, after 4 cycles, the relative activity of mhNFs biocatalysts were 19.8%.